Nucleotide sequence analysis of Adh genes estimates the time of geographic isolation of the Bogota population of Drosophila pseudoobscura. - Schaeffer, S W (1991)
The population of Drosophila pseudoobscura at Bogota, Columbia, is geographically and partially reproductively isolated from populations in the main body of the species in North America. The degree of genetic differentiation and time of divergence between populations at Bogota and Apple Hill, CA, were estimated by comparison of 3388 nucleotides in the alcohol dehydrogenase region (Adh and Adh-Dup genes) of 18 strains. Of the 146 polymorphic nucleotide sites detected, 68 and 31 were unique to the Apple Hill and Bogota samples, respectively, and 53 were shared. On the basis of an observed net divergence per nucleotide site of 0.264% between the two samples, the Bogota and North American populations were estimated to have been separated for at least 155,000 years. This divergence time suggests that D. pseudoobscura extended its range from North America to South America in a period of Pleistocene glaciation, when habitat suitable for the species presumably existed in lowland Central America.